The effect of solvent composition on vancomycin hydrochloride and free base vancomycin release from in situ forming implants. (24th June 2016) - Darestani‐Farahani, M.; Vasheghani‐Farahani, E.; Mobedi, H.; Ganji, F.
Abstract : In situ forming drug delivery systems that are formed by solvent‐induced phase inversion have attracted extensive attention in sustained delivery of peptides and proteins. Based on the findings of our previous studies, N ‐methyl‐2‐pyrrolidone (NMP) and acetone are two solvents that could improve the release profile of vancomycin from in situ forming systems based on poly(D, L‐lactide‐co‐glycolic acid). In this study, the effect of different compositions of these solvents on the release profile of hydrochloride and free base forms of vancomycin was investigated. To this end, several formulations with vancomycin (either hydrochloride or free base form) and different proportions of NMP and acetone were prepared. The cumulative drug release at specified time was determined and tested against conventional kinetic models. The surface and cross‐sectional morphology of implants were investigated by SEM. The experimental results showed that as solvent composition changed, the amount of vancomycin release during the first 12 h changed, too. The use of free base vancomycin resulted in an extended vancomycin release profile with less initial burst release. The formulation containing free base vancomycin and mixed solvents of acetone and NMP in 2:1 ratio released 70% of loaded drug in 6 weeks with near zero‐order kinetic. The best kinetic model to fit the in vitro release profiles was found to be Peppas–Sahlin model. Copyright © 2016 John Wiley & Sons, Ltd.